Regression of Peripheral Subclinical Enthesopathy in Therapy‐Naive Patients Treated With Ustekinumab for Moderate‐to‐Severe Chronic Plaque Psoriasis: A Fifty‐Two–Week, Prospective, Open‐Label Feasibility Study. Issue 4 (4th March 2019) - Savage, Laura; Goodfield, Mark; Horton, Laura; Watad, Abdulla; Hensor, Elizabeth; Emery, Paul; Wakefield, Richard; Wittmann, Miriam; McGonagle, Dennis
Abstract : Objective: To investigate whether sonographically determined subclinical enthesopathy in patients with moderate‐to‐severe psoriasis regresses with the use of ustekinumab therapy for skin disease. Methods: Seventy‐three patients with moderate‐to‐severe psoriasis, who were not treated with systemic therapy and did not have symptoms of psoriatic arthritis (PsA), and 23 healthy volunteers were screened by ultrasound for subclinical enthesitis. Subsequently, 23 patients with psoriasis whose ultrasound results showed inflammatory changes were treated with ustekinumab for 52 weeks. The evolution of sonographic abnormalities of the upper and lower limb entheses was assessed using an extensive gray‐scale and power Doppler (PD) ultrasound protocol at weeks 0, 12, 24, and 52. For each parameter, a gray‐scale or PD ultrasound score of >0 was determined to be abnormal, and a summative score based on the Glasgow Ultrasound Enthesitis Scoring System was calculated. Results: Of all the patients with psoriasis screened using ultrasound, 49.3% had at least 1 inflammatory entheseal abnormality. Mean ± SD inflammation scores were higher in the patients with psoriasis compared with the healthy volunteers (9.9 ± 6.6 versus 1.0 ± 1.4). With treatment, the mean inflammation scores decreased significantly by 42.2% from week 0 to week 24 (–4.2 [95% confidence interval –6.3, –2.1]; P < 0.001) and by 47.5% by week 42 (–4.7 [95% confidence interval –7.1, –2.3]; P = 0.001). Entheseal structural abnormalities did not change significantly during treatment. Conclusion: Within 12 weeks of treatment, interleukin‐12 (IL‐12)/IL‐23 inhibition for psoriasis appears to suppress subclinical enthesopathy, and the suppression is maintained through week 52. Further longitudinal studies are needed to determine whether therapy initiated for skin disease may prevent the development of PsA.